2016
DOI: 10.1002/ajhb.22837
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein increases with gestational age during pregnancy among Chinese women

Abstract: We concluded that CRP increased with gestational age among healthy Chinese women who delivered healthy infants. Am. J. Hum. Biol. 28:574-579, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…In fact, CRP levels above normal ranges are recognized as a common state in pregnancy, reflecting the adaptations that occur in maternal immunity and which are necessary for the support of the unborn child. Thus, CRP increase is natural in a healthy pregnancy, rising with advancing gestational age [34,40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, CRP levels above normal ranges are recognized as a common state in pregnancy, reflecting the adaptations that occur in maternal immunity and which are necessary for the support of the unborn child. Thus, CRP increase is natural in a healthy pregnancy, rising with advancing gestational age [34,40]. …”
Section: Discussionmentioning
confidence: 99%
“…The inferred presence of infection was defined by the cutoff value equal or higher than (≥)5 mg/L for the acute-phase reactant C-reactive protein (CRP) [33,34]. CRP was determined by Tina-quant CRP (Latex)-HS immunoturbidimetric assay (BM Hitachi 917 Roche, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, an increase in CRP levels may occur in many other situations as well as in the presence of infection, including during a normal or physiological pregnancy when levels reflect the adaptations needed to support the fetus. These adaptations occur during the process of maternal immune tolerance, particularly as gestational age increases [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of important covariates of inflammation that were not consistently measured in the surveys included indicators of access to clean water and sanitation and nonmalarial infections (e.g., HIV and soil-transmitted helminths). We did not include pregnant women in our analysis, which is a research gap because of the shown increase in inflammatory proteins in pregnancy and their potential link to adverse maternal and infant health outcomes (32, 33). Further, breastfeeding and lactation were included as binary variables across the full age distribution and did not account for a differential association across the age distribution.…”
Section: Discussionmentioning
confidence: 99%